THE EFFECT OF ACETIC ACID ON CHARACTERISTICS OF TUNA FISH SKIN GELATIN - Meity Sompie, A.T. Agustin & (Proceeding of International Congress, 2014)
This research was aimed to study the influence of acetic acid on characteristics of tuna fish skin gelatin.This study were used tuna fish skin which soaked in 1%, 2 % and 3 % CH3COOH (acetic acid). Statisticalanalysis were carried out by one Anova and the mean difference was tested using Duncans MultipleRange Test. The result showed that acetic acid concentration had significant effect (P<0.01) on the gelstrength 20.020 to 20.021g Bloom, yield 12 to 16%, viscosity :2.3 to 3.0 cP and pH value of tuna fish skingelatin. It was concluded that tuna fish skin gelatin with acetic acid concentration 1%, 2% and 3 % hadsimilar characteristics to the commercial gelatin but the optimum production was obtained from 3 %acetic acid.Keywords: Tuna fish, skin, gelatin, curing, acetic acid